How conservation matters: Ethnographic explorations of historic building renovation. (March 2019) - Yarrow, Thomas
This article focuses on ideas of historic conservation, examining the multiple ways in which these are made to matter through practices of renovation. Bypassing normatively inflected literatures on heritage, the author adopts a more 'agnostic' ethnographic approach, highlighting how conservation involves an imperative of continuity that is elaborated in a multiplicity of ways by conservation and construction professionals, and inhabitants of old buildings. This focus brings to light a series of dynamics that have received limited attention, demonstrating how conservation is practically substantiated in a range of ways including materially, bodily, emotionally, ethically and conceptually.